2018
DOI: 10.1108/jocm-02-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Change leadership in the 21st century

Abstract: Purpose The purpose of this paper is to examine the field of change leadership at the beginning of the twenty-first century. Design/methodology/approach The meta-framework presented in this study is a review of the field of change leadership over a 16-year period. The authors reviewed hundreds of peer-reviewed refereed journal articles and books. Findings The authors identify the key themes in the study of change leadership through the lens of content and process frames of reference. Originality/value Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 42 publications
2
53
0
4
Order By: Relevance
“…Higher education institutions (HEIs) are complex adaptive systems (CAS) comprised of independent agents combining in diverse organisational relationships and networks. Given the dynamic and non‐linear nature of such systems, scholars have argued that HEIs need change management that focuses on emergent, flexible and adaptable change rather than on planned change (Dumas & Beinecke, ; Todnem By, ). That is to say, HEIs need to be prepared for unanticipated consequences of innovations internally and fast‐changing environments externally.…”
Section: Adopting Learning Analytics In a Complex Adaptive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions (HEIs) are complex adaptive systems (CAS) comprised of independent agents combining in diverse organisational relationships and networks. Given the dynamic and non‐linear nature of such systems, scholars have argued that HEIs need change management that focuses on emergent, flexible and adaptable change rather than on planned change (Dumas & Beinecke, ; Todnem By, ). That is to say, HEIs need to be prepared for unanticipated consequences of innovations internally and fast‐changing environments externally.…”
Section: Adopting Learning Analytics In a Complex Adaptive Systemmentioning
confidence: 99%
“…This is particularly pertinent to HEIs in the UK where funding policy and metrics of success have been noted to discourage innovation and risk‐taking among HEIs (Norton & Carter, ); and where Brexit turmoil has worsen the situation further (Universities UK, ). Considering current changing environments, studies have suggested that leadership should move away from being hierarchical and leader‐centred, to being participative, dispersed, and collective, so as to shift the attention from individual leaders to organisation processes (Bento, ; Dumas & Beinecke, ). Instead of convincing people to follow a visionary leader, institutions should seek innovations to address pertinent challenges by distributing power across sub‐networks and support subordinates to take leading roles in their areas of influence.…”
Section: Adopting Learning Analytics In a Complex Adaptive Systemmentioning
confidence: 99%
“…Apesar de a liderança despontar como elemento crucial diante dos desafios vividos pela sociedade e pelas organizações em geral (FERNANDES; SIQUEIRA; VIEIRA, 2014; GANDOLFI; STONE, 2017), as mudanças substanciais do século XXI revelam que muitos modelos populares de liderança se mostram insuficientes para lidar com a complexidade deste tempo (MALVEZZI, 2011;DUMAS;BEINECKE, 2018).…”
Section: Liderança Servidoraunclassified
“…Organizational leadership are more aware of trends, crises, and evolutions in their organizational environments, which prepare them to be resilient and adaptive to changes. 33 Research on nursing homes 34 suggests that the presence of change leadership and an organizational climate of innovation are likely to assist organizations preparing for change.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%